016 Associations between Circadian Melatonin and Temperature Amplitudes during Constant Routine. (3rd May 2021) - Rodheim, Katrina; Jung, Christoper; Wright, Kenneth
Abstract: Introduction: Circadian amplitude measures the strength or robustness of a rhythm and changes in amplitude may have implications for health. Large individual differences in melatonin amplitude are recognized. Here we aimed to determine the strength of relationships between melatonin and the core body (CBT) and distal-proximal skin temperature gradient (DPG) amplitudes during a constant routine protocol. Additionally, we determined the best fitting harmonic model for the DPG circadian rhythm. Methods: 17 young healthy adults [13 males (22.3±3.9yr;mean±SD)] completed a 28-hr constant routine protocol after maintaining 8h habitual sleep schedules for one week at home. Endogenous circadian amplitudes of melatonin and CBT were fit with standard three- and dual-harmonic linear regression models, respectively. The DPG amplitude was analyzed with both dual and three-harmonic regression models to determine which model produced the best fit. Results: The DPG was best fit by a three-harmonic regression model with significantly lower standard deviation and higher signal-to-noise ratio compared to the 2-harmonic model (both p<0.05) as well as by visualization of the fitted curves. Melatonin, CBT and DPG amplitudes were not found to be associated with each other during constant routine (all r<0.37; all p>0.10). Conclusion: While it is common for melatonin and body temperature circadian phase estimates to be used interchangeably, non-significant findings for associations between circadian amplitudes of melatonin, CBT and DPG indicate that these markers may not provide similar information about circadian amplitude. Further, research is needed to explore possible associations between individual differences in melatonin, CBT and DPG amplitudes with other physiological and behavioral outcomes to determine which measure(s) of circadian amplitude may be functionally relevant. Support (if any): NIH R01 HL081761